Spectroscopic and photometric analysis of the early-type spectroscopic binary HD 161853 in the centre of an H ii region (Research Note) - Gamen, Roberto Claudio (2015)
Aims. We study the O-type star HD 161853, which has been noted as a probable double-lined spectroscopic binary system. Methods. We secured high-resolution spectra of HD 161853 during the past nine years. We separated the two components in the system and measured their respective radial velocities for the first time. Results. We confirm that HD 161853 is an ~1 Ma old binary system consisting of an O8 V star (MA,RV ≥ 22 M⊙) and a B1–3 V star (MB,RV ≥ 7.2 M⊙) at about 1.3 kpc. From the radial velocity curve, we measure an orbital period P = 2.66765 ± 0.00001 d and an eccentricity e = 0.121 ± 0.007. Its V-band light curve is constant within 0.014 mag and does not display eclipses, from which we impose a maximum orbital inclination i = 54 deg. HD 161853 is probably associated with an H ii region and a poorly investigated very young open cluster. In addition, we detect a compact emission region at 50 arcsec to HD 161853 in 22 μm-WISE and 24 μm-Spitzer images, which may be identified as a dust wave piled up by the radiation pressure of the massive binary system.